2013
DOI: 10.4049/jimmunol.1201887
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Inhibition of Serotonin Type 7 (5-HT7) Receptor Function Modulates Immune Responses and Reduces the Severity of Intestinal Inflammation

Abstract: Mucosal inflammation in conditions ranging from infective acute enteritis or colitis to inflammatory bowel disease is accompanied by alteration in serotonin (5-hydroxytryptamine [5-HT]) content in the gut. Recently, we have identified an important role of 5-HT in the pathogenesis of experimental colitis. 5-HT type 7 (5-HT7) receptor is one of the most recently identified members of the 5-HT receptor family, and dendritic cells express this receptor. In this study, we investigated the effect of blocking 5-HT7 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 70 publications
6
89
3
1
Order By: Relevance
“…In accordance with this hypothesis, a previous study reported a reduced ability of maturing Cdc42-deficient dendritic cells to upregulate CCR7 expression (Luckashenak et al, 2013). Furthermore, it has been demonstrated that 5-HT 7 R-mediated signaling regulates the activation of NF-κB in colon-derived dendritic cells (Kim et al, 2013). By contrast, inhibition of NF-κB has been shown to significantly reduce the induction of CCR7 expression in monocyte-derived dendritic cells (van de Laar et al, 2010).…”
Section: Discussionsupporting
confidence: 52%
“…In accordance with this hypothesis, a previous study reported a reduced ability of maturing Cdc42-deficient dendritic cells to upregulate CCR7 expression (Luckashenak et al, 2013). Furthermore, it has been demonstrated that 5-HT 7 R-mediated signaling regulates the activation of NF-κB in colon-derived dendritic cells (Kim et al, 2013). By contrast, inhibition of NF-κB has been shown to significantly reduce the induction of CCR7 expression in monocyte-derived dendritic cells (van de Laar et al, 2010).…”
Section: Discussionsupporting
confidence: 52%
“…Histological damage scoring of the colon was performed blindly on formalin-fixed, paraffin-embedded sections stained with H&E using previously described scoring criteria (20,51).…”
Section: Methodsmentioning
confidence: 99%
“…5-HT 7 receptors are also found on macrophages and have been implicated as a potential target for treating intestinal inflammatory disorders. 59,60 Serotonin induces desensitization (tachyphylaxis) at different rates and magnitudes in different tissues and this is the case with 5-HT 4 receptor agonists as highlighted by prucalopride desensitizing pig atrium but not pig stomach 5-HT 4 receptors. 61 Different GRKs are associated with 5-HT 4 receptor desensitization depending on the tissue type in the rat and significantly these GRKs are not necessarily those predicted by studies using recombinant proteins expressed in cell culture.…”
Section: Discussionmentioning
confidence: 99%